Heterogeneity of market power: firm-level evidence - Yilmaz, Ensar; Kaplan, Zeynep (SPRINGER, 2022)
Recent work in macroeconomics argues that firm market power dramatically increased since the 1980s in the world. The evolution of product markups has important implications for macroeconomic dynamics. In this paper, we start to document the main patterns of markups in an emerging economy like Turkey using production function approach and dynamic panel approach. Our empirical analysis is based on large-scale firm-level reliable panel data, which enables us to provide sound results in several aspects. In this way, we trace up the facts on the cross section and time series of markups of the firms in manufacturing sector in Turkey over the period 2005-2015. Then, we use our markup estimates to discuss the connection between markup and some selective variables such as firm size, labor share, profitability, and reallocation. It is mainly seen that large firms are critical in determining these variables. This illustrates the significant amount of heterogeneity among the firms in Turkey.
Keywords: Market power; Markups; Profitability; Labor share; UNITED-STATES; PANEL-DATA; PRICES; COST; RISE; Business & Economics